1926
DOI: 10.1017/s0025315400007189
|View full text |Cite
|
Sign up to set email alerts
|

On the Penetration of Light into Sea Water.

Abstract: 1. A description is given of some measurements of the penetration of light into sea-water carried out near Plymouth in the autumn of 1925 by means of photo-electric cells, the current through the cell being, measured by a method, previously described, which is not affected by the motion of the ship.2. The absorption coefficients found for off-shore waters down to 30 metres are smaller than the average of those found by several recent observers in various localities, but considerably larger than those found by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1928
1928
1989
1989

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…The validity of this approximation has been shown in many ecological investigations (e.g. Poole and Atkins 1926;Aberg and Rodhe 1942;Kuroiwa et al 1983). Narrow spectral bands should be used and measurements must be made at various depths (Smith 1968;Dubinsky and Berman 1979).…”
Section: Theorymentioning
confidence: 77%
“…The validity of this approximation has been shown in many ecological investigations (e.g. Poole and Atkins 1926;Aberg and Rodhe 1942;Kuroiwa et al 1983). Narrow spectral bands should be used and measurements must be made at various depths (Smith 1968;Dubinsky and Berman 1979).…”
Section: Theorymentioning
confidence: 77%
“…There is uncertainty about the light levels where 1640 a disk disappears and also about the underlying theory of the Secchi disk. Poole andAtkins (1926, 1929), who were the first to compare measurements of underwater light with transparency measurements, assumed that transparency is inversely proportional to the vertical attenuation coefficient for diffuse underwater sunlight, as predicted by the Lambert-Bouguer law. Many subsequent workers have adopted this assumption, but others (Tyler 1968;Holmes 1970) assumed that transparency depends on the sum of diffuse attenuation and beam attenuation, as proposed by Duntley (1963) and Preisendorfer ( 19 8 6).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…They consider the length of the day, rather than the amount of sunshine, to be the most important factor. Working with a muffed glass receiving surface mounted over a photoelectric cell, Poole and Atkins (1926) found that in September-which may be considered as more or less comparable to April~the ratio of the reading with the cell exposed horizontally to full sunlight to that obtained when the direct rays of the sun were cut off, so that the cell received diffuse light only, was about 3.5 under clear conditions, falling to about two with weak sunlight and hazy or cloudy sky, so that the diffused light was high. These figures are not accurate measures of the ratio of total light to diffuse light, since the average obliquity of the diffuse light was not identical with that of the sun's rays, but it serves well as a comparison.…”
mentioning
confidence: 99%